The cytokine response element of the rat alpha 1-acid glycoprotein gene is a complex of several interacting regulatory sequences. - Won, K A (1990)
Expression of the rat alpha 1-acid glycoprotein gene is stimulated by interleukin-1 (IL-1) and interleukin-6 (IL-6) and is synergistically enhanced by the combination of the two. The distal regulatory element (DRE), a 142-base-pair (bp) sequence located 5 kilobase pairs upstream of the transcriptional start site, appears to be crucial for this cytokine response. The cytokine-specific regulatory sequences within the DRE have been identified by inserting individual DRE subregions, selected combinations of these, or a few linker mutated fragments into a plasmid containing an enhancerless simian virus 40 promoter linked to the chloramphenicol acetyltransferase gene. The regulatory activity was determined in transiently transfected human and rat hepatoma cells. The IL-1 response region was confined to the 5'-most 62 bp of the DRE, and its function seemed to depend on at least two separate components. The same region was also responsive to phorbol ester treatment. The IL-6 regulatory function was dependent on a 54-bp sequence located within the 3' half of the DRE. When the IL-1 response region was recombined with the IL-6 regulatory region of the DRE or with IL-6 response elements of other plasma protein genes, a strong cooperative action by IL-1 and IL-6 was achieved. The functional DRE sequences were recognized by nuclear proteins extracted from rat liver and hepatoma cells. However, no cytokine-inducible binding activity was detectable, which suggests that transcriptional regulation through the DRE might be controlled by posttranslational modification of constitutively bound trans-acting factors.